Update on pathology of retinoblastoma - Singh, Lata (Int J Ophthalmol, 2018)
Retinoblastoma is caused by mutational inactivation of both alleles of the RB1 gene, which maps to chromosome 13q14 and encodes retinoblastoma protein that acts as a tumor suppressor. Histopathological high-risk features of retinoblastoma are predictive of metastasis or local recurrence. The focus of this update is to emphasize the recent advances in pathology, various molecular key pathways and genome wide approaches for newer potential therapeutic future targets associated with retinoblastoma tumor biology. This review article highlights the new biomarkers expressed by the retinoblastoma tumor for the better survival of patients.